2022
DOI: 10.1161/circgen.120.002981
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation of A Nation-Wide Dutch Pediatric DCM Cohort: The Use of Genetic Testing in Risk Stratification

Abstract: Background: This study aimed to describe the current practice and results of genetic evaluation in Dutch children with dilated cardiomyopathy and to evaluate genotype-phenotype correlations that may guide prognosis. Methods: We performed a multicenter observational study in children diagnosed with dilated cardiomyopathy, from 2010 to 2017. Results: One hundred forty-four children were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…A recent GWAS meta-analysis concluded that this kinase holds a direct phenotypic effect in the heart, causing reduced left ventricular systolic function and cardiomyocyte cell cycle arrest [39]. An in-vivo model of CDKN1A knockout mice developed cardiac hypertrophy and HF [51]. A phenome-wide association study (PheWAS; comparing a trait in individuals with or without a reported clinical outcome) further identified the CDKN1A locus as significantly associated with HCM and ECG traits (PR interval and QRS duration) [52].…”
Section: Common Dna Variants Associated With Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…A recent GWAS meta-analysis concluded that this kinase holds a direct phenotypic effect in the heart, causing reduced left ventricular systolic function and cardiomyocyte cell cycle arrest [39]. An in-vivo model of CDKN1A knockout mice developed cardiac hypertrophy and HF [51]. A phenome-wide association study (PheWAS; comparing a trait in individuals with or without a reported clinical outcome) further identified the CDKN1A locus as significantly associated with HCM and ECG traits (PR interval and QRS duration) [52].…”
Section: Common Dna Variants Associated With Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…In a subcohort of more complex cases, 26/46 (57%) received a change in management and risk stratification ( 25 ). Pediatric DCM cases with a pathogenic or likely pathogenic variant had 2.8-times increased risk of death or heart transplant, suggesting the importance of genetic testing for predicting clinical outcomes ( 26 ). In 2021, Murdock, et al reported on a next-generation sequencing (NGS)-based genetic testing panel that returned results with clinical management implications for 32% of patients seen in institutionally affiliated adult cardiology clinics ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that 27% to 54% of iDCM cases have a genetic component. 5–8 Common mutations in genes related to sarcomere structure (such as MYH7 , MYBPC3 , and TNNT2 ), nuclear envelope (such as LMNA ), and cytoskeleton (such as DES and DMD ) have been described previously. 4–8 Increased widespread genetic testing abilities have begun to help identify novel classes of genes suspected to be responsible for iDCM, greatly expanding our understanding of the pathogenesis of this condition.…”
mentioning
confidence: 98%
“…nfantile dilated cardiomyopathy (iDCM) is a rare condition with multiple pathogeneses that results in substantial morbidity and mortality. [1][2][3][4][5] Of the studied infantile cardiomyopathies, dilated cardiomyopathy is the most prevalent, responsible for ≈50% of infantile/pediatric cardiomyopathy cases. 2 Such cases are particularly difficult to manage, and many will necessitate heart transplant as the final management approach.…”
mentioning
confidence: 99%